From the Ground Up : Translating Geography into Community through Neighbor Networks - Grannis, Rick, 1965- (Book collections on Project MUSE., 2009)
Where do neighborhoods come from and why do certain resources and effects--such as social capital and collective efficacy--bundle together in some neighborhoods and not in others? From the Ground Up argues that neighborhood communities emerge from neighbor networks, and shows that these social relations are unique because of particular geographic qualities. Highlighting the linked importance of geography and children to the emergence of neighborhood communities, Rick Grannis models how neighboring progresses through four stages: when geography allows individuals to be conveniently av.